Strategies for estimating atmospheric water vapour using ground-based GPS receivers in Australia - Agustan (Curtin University, 2004)
The Global Positioning System (GPS) of navigation satellites was first developed for global navigation and position determination purposes. Signals from satellites are delayed by the Earths neutral atmosphere on propagating to ground-based receivers, termed the tropospheric delay. Although an unwanted term for precise positioning, the tropospheric delay may be converted to atmospheric water vapour, which is a vital parameter for weather forecasting.This research investigates the optimum GPS processing strategy to estimate atmospheric water vapour derived from ground-based GPS receivers particularly in the Australian region. For this purpose, GPS data observations from GPS permanent stations across Australia, mainly from the Australian Regional GPS Network, will be processed using scientific GPS software in post-processed mode and near real-time mode.This research shows that by applying high accuracy GPS data processing, the tropospheric delay could be estimated precisely. The quality of GPS data processing is indicated by the station coordinates repeatability since the coordinates can gauge at least a coarse assessment of the ability of the processing method to estimate the tropospheric delay.The precipitable water can be estimated from the wet component after separating the tropospheric delay into dry and wet components. High accuracy GPS data processing is dependent on the best choice of processing strategies, and the correct application of error-correction models and a priori constraints. This research finds that the GPS- PW estimation agrees with Radiosonde-PW estimation with an average of standard deviation at 2.5mm level for post-processed strategy and 2.8mm for near real-time strategy. The standard deviation of tropospheric parameter estimates is 1.1mm for post-processed strategy and 1.5mm for near real-time strategy.